Auditoría de gestión al departamento financiero del Gobierno Autónomo Descentralizado Municipal del cantón Salcedo, período comprendido del 1 de enero al 31 de diciembre del 2014 - Taipe Yanchaguano, Blanca Susana (2016)
The research general aim objective was; to apply an audit of managment to the financial departament decentralized autonomous municipal government in Salcedo canton to assess the degree of efficiency, effectiveness and economy handled the resources available during the period 2014, with the aim to issue a professional technical opinion. The methods and techniques used for data collection were the interview, survey and indicators. With the exam that has been done, it was determined that the municipality does not have a training program for staff , who fails to comply with the functions of the functional organic, and especially the financial departament do not have indicators directing, that allows to measure whether resources are used properly , by that reason the propousal was given to the mayor so that, it is generated other mechanisms that allow to correct these weaknesses and guarantee the staff’s appropiated operation that works at municipality….